Assessment of quality of life related to health in patients with fibromyalgia - Ana María Martín Nogueras; Juliana Maria de Sousa Pinto; José Ignacio Calvo Arenillas (Universidade de Fortaleza, 2010)
Objectives: To determine the impact that fibromyalgia (FM) has on quality of life; to compare the quality of life of patients with fibromyalgia with the healthy Spanish population and to know the correlation and sensibility of two instruments of quality of life in FM. Method: A cross-sectional and observational study. Twenty-seven subjects joined in (25 women and 2 men) with a mean age of 50.5 years (SD 7.9), belonging to the Salmantina Association ofFibromyalgia and Chronic Fatigue. The Spanish versions of the Nottingham Health Profile (NHP) and the the Short-Form 36 (SF36) were used to study quality of life. Results: High scores were obtained in the "Energy", "Pain", "Sleep" and "Physical mobility" dimensions of the NHP and low scores in the "Physical problems", "Pain", "Vitality" and "General health perception" dimensions of the SF-36. Statistical significant differences were found in all dimensions comparing to the healthy Spanish population. The following dimensions were negatively statistically correlated: "Energy"(NHP)-"Vitality" (SF-36); "Pain"(NHP)- "Physical function", "Pain and Vitality" (SF-36); "Physical mobility" (NHP)-"Physical function and Physical problems" (SF-36); "Emotional reactions" (NHP)- "Mental health", "Emotional problems" and "General health" (SF-36). The SF-36 is more sensitive than the NHP to evaluate the deterioration of the fibromyalgia. Conclusions: The fibromyalgia produces a significant deterioration in quality of life that can be assessed by the dimensions of the NHP and the SF-36.